A tungsten diboride-silicon carbide composite powder with uniform size and a composite ceramic and a preparation method and application thereof

Tungsten diboride-silicon carbide composite powder was prepared by using tungsten trioxide, boron carbide, silica and carbon source powder, and through discharge plasma sintering technology, the density sintering difficulty and fracture toughness of tungsten diboride ceramics were solved. The problem of low is that the low cost and rapid preparation of tungsten diboride-silicon carbide composite ceramics with high density and high fracture toughness can be achieved.

CN116495739BActive Publication Date: 2025-02-11GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310514475.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-08
Publication Date
2025-02-11
Estimated Expiration
2043-05-08

AI Technical Summary

Technical Problem

The existing tungsten diboride ceramics have problems such as difficulty in densification and sintering and low fracture toughness. They have high production cost, complex process and uneven distribution of purity and particle size.

Method used

Using tungsten trioxide, boron carbide, silica and carbon source powder as raw materials, the uniform size of tungsten diboride-silicon carbide composite powder was prepared by high-energy ball milling mixture and heat treatment under vacuum, and then discharged Plasma sintering gives dense complex phase ceramics.

Benefits of technology

The high density (>97%) and high fracture toughness (5.4±0.7MPa·m1/2) of tungsten diboride ceramics were achieved, which reduced the preparation cost and process complexity, and obtained a composite powder with a small and uniform particle size. body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004218578560000011
    Figure HDA0004218578560000011
  • Figure HDA0004218578560000012
    Figure HDA0004218578560000012
  • Figure HDA0004218578560000021
    Figure HDA0004218578560000021
Patent Text Reader

Abstract

The present invention belongs to the technical field of inorganic non-metallic hard material preparation, and discloses a tungsten diboride-silicon carbide composite powder and a composite ceramic with uniform size, a preparation method and an application. Tungsten trioxide powder, boron carbide powder and carbon source powder are weighed in a molar ratio of 2: (1-1.2): (4.7-5), the content of silicon dioxide powder and carbon source powder is adjusted to the required ratio of 5-50% for in-situ synthesis of silicon carbide volume fraction, and then the silicon dioxide powder and carbon source powder are weighed in a molar ratio of 1: 3, ball milled and mixed evenly, heated to 1300-1500℃ in a vacuum state for 0.5-2 hours, ground and sieved, and a tungsten diboride-silicon carbide composite powder with high purity and no impurities and fine particle size is obtained. The composite powder is sintered in a spark plasma sintering furnace to obtain a tungsten diboride-silicon carbide composite ceramic, which has high density and excellent mechanical properties and can be applied to the fields of wear-resistant materials, corrosion-resistant materials and cutting tools.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic hard material preparation, and particularly relates to a preparation method and application of a tungsten diboride-silicon carbide composite powder with uniform size and a composite ceramic thereof. Background Art

[0002] Transition metal borides have excellent mechanical properties such as high melting point, high hardness and high wear resistance, as well as good electrical conductivity and chemical stability. They can be synthesized under non-high pressure conditions and are of great value in the development and application of cutting tools, wear-resistant parts and electrode materials. The transition metal borides reported so far mainly include borides of Ti, Zr, Hf, Ta and W, among which zirconium diboride and hafnium diboride have more mature research and application in basic research and application technology. Compared with zirconium diboride and hafnium diboride, the sintering temperature of tungsten diboride (1500-1600℃) is much lower than that of zirconium diboride and hafnium diboride (1900-2000℃), so the preparation cost is lower. Moreover, the Vickers hardness of tungsten diboride can reach 24.5GPa under a load of 4.9N, which is better than zirconium diboride and hafnium diboride ceramics, and has more application potential as a hard material and wear-resistant material. However, the current single-phase tungsten diboride ceramics generally have low relative density, poor sintering performance, and poor fracture toughness (4.3±0.4MPa·m 1 / 2 ) problem.

[0003] High-purity, fine-particle high-quality powders are the basis for obtaining densified ceramics with excellent performance. The main preparation methods of tungsten diboride powder are: single-element direct synthesis method (Cao Xiaozhou, Xue Xiangxin, Yang He, et al. Rare Metal Materials and Engineering. 2014, 43, 1987-1990.), high-temperature self-propagation method (B. Derin, S. Yazici. Materials Science (Medziagotyra). 2018, 24, 35-38.), boron thermal reduction method (B. Dai, X. Ding, X. Deng, et al. Ceramics International. 2020, 46, 14469-14473) and boron thermal / carbon thermal reduction method (Y. Long, B. Liu, S. Lin, et al. Journal of the European Ceramic Society. 2022, 42, 5229-5237). The cost of single substance direct synthesis method and boron thermal reduction method is relatively high, the powder synthesized by high temperature self-propagating method has low purity and uneven powder particle size distribution, and the tungsten diboride powder obtained by boron thermal / carbothermal reduction method has low cost, high purity and small particle size. However, the density of unidirectional ceramics obtained by sintering the tungsten diboride powder synthesized by boron thermal / carbothermal reduction method can only reach about 93% at present.

[0004] Adding a second phase material is a simple and effective means to improve the sintering properties and mechanical properties of transition metal borides, among which silicon carbide is a commonly used second phase material. Many studies have shown that adding silicon carbide can improve the sintering properties and mechanical properties of transition metal boride ceramics. Therefore, exploring a cheap and efficient preparation process for tungsten diboride-silicon carbide composite materials to improve the sintering properties and mechanical properties of tungsten diboride has important practical significance for promoting its application.

[0005] However, there is no research on tungsten diboride-silicon carbide composite materials, but there are reports on other transition metal borides and silicon carbide composite materials, including several studies on the in-situ preparation of zirconium diboride-silicon carbide composite materials by combining boro-thermal / carbon-thermal reduction. For example, Chinese patent document (CN102826851A) discloses a method for preparing a zirconium boride-silicon carbide composite material with high temperature resistant powder. Zircon sand, zircon or zirconium silicate are used as the main raw materials, boron carbide, borax or boron mud is used as the boron source, carbon black, coke or activated carbon is used as the raw material, alkaline earth metal oxides are added as additives, ball milling and mixing are performed, and the zirconium boride-silicon carbide composite powder is obtained by reacting at 1400-1800°C for 0.1-100 hours in a reducing atmosphere. This method has low cost and short process flow, but it requires additional addition of alkaline earth metal oxides, and the obtained powder contains zirconium carbide impurities. Zeng et al. (Y. Zeng, J. Liu, F. Liang, et al. Journal of the American Ceramic Society. 2019, 102, 2426-2439) used zirconium dioxide, boron carbide, silicon dioxide and amorphous carbon as raw materials, combined with NaCl / KCl molten salt and microwave heating at 1100-1200°C for 20 minutes to obtain zirconium diboride-silicon carbide composite materials, and finally obtained dense (relative density 99.2%) and excellent performance (Vickers hardness 24.5 GPa, fracture toughness 4.8 MPa·m 1 / 2) zirconium diboride-silicon carbide composite ceramics. However, this method is complicated and time-consuming, and is prone to residual molten salts such as NaCl and KCl. Chinese patent literature (CN108622911B) also discloses a method for preparing ultrafine zirconium diboride-silicon carbide composite powder. This method uses zirconium dioxide, boron carbide, carbon black and silicon powder as raw materials, calcined at 1300-1600°C and protective gas for 30-90 minutes, to obtain a zirconium diboride-silicon carbide composite powder with small particle size and uniform morphology. However, the cost of single silicon powder is relatively high and an oxide film is easily formed on the surface. Xie et al. (B. Xie, L. Ma, Y. Liu, et al. Ceramics International. 2018, 44, 19522-19525.) synthesized zirconium diboride-silicon carbide composite powder at 1300-1600°C using zirconium dioxide, boron carbide, silicon dioxide and carbon black as raw materials. During the synthesis process, the boron oxide generated by the reaction of zirconium dioxide and boron carbide will react with the silicon dioxide in the raw materials to form borosilicate glass. Borosilicate glass will inhibit the formation of silicon carbide while promoting the growth of zirconium diboride grains. Therefore, the particle size distribution of synthesized zirconium diboride and silicon carbide is uneven. The particle size of zirconium diboride is relatively large, 2-3μm, and the particle size of silicon carbide is small, only 30-50nm.

[0006] 7ZrO2+5B4C=7ZrB2+3B2O3+5CO(g)#(1)

[0007] ZrO2+B2O3+5C=ZrB2+5CO(g)#(2)

[0008] Therefore, it is urgent to develop a method for preparing tungsten diboride-silicon carbide composite powder that is simple, convenient, low-cost, has a short production cycle, small powder particle size, uniform size and high purity, so as to solve the problem of difficult densification and low fracture toughness of tungsten diboride ceramics. Summary of the invention

[0009] In order to solve the shortcomings and deficiencies of the above-mentioned prior art that tungsten diboride is difficult to densify and sinter, and at the same time improve the fracture toughness of tungsten diboride ceramics, the primary purpose of the present invention is to provide a simple and rapid preparation method for tungsten diboride-silicon carbide composite powder with uniform size; the method uses tungsten trioxide powder, boron carbide powder, silicon dioxide powder and carbon source powder as raw materials, performs high-energy ball milling mixing on them, and then performs heat treatment under vacuum to obtain tungsten diboride-silicon carbide composite powder with uniform size.

[0010] Another object of the present invention is to provide a method for synthesizing tungsten diboride-silicon carbide composite powder with uniform size.

[0011] Another object of the present invention is to provide an application of the above-mentioned tungsten diboride-silicon carbide composite powder with uniform size.

[0012] Another object of the present invention is to provide a tungsten diboride-silicon carbide composite ceramic with a dense grain size and a small grain size obtained by spark plasma sintering using the above-mentioned tungsten diboride-silicon carbide composite powder with uniform size.

[0013] The purpose of the present invention is achieved through the following technical solutions:

[0014] A method for preparing a tungsten diboride-silicon carbide composite powder with uniform size comprises the following steps:

[0015] (1) Weigh tungsten trioxide powder, boron carbide powder and carbon source powder A in a molar ratio of 2:(1-1.2):(4.7-5); then weigh silicon dioxide powder and carbon source powder B in a molar ratio of 1:3; fully mix all the above-mentioned powders by ball milling at room temperature using a high-energy ball mill to obtain a mixed powder; the weighed amounts of the silicon dioxide powder and the carbon source powder B are calculated based on the volume fraction of the silicon carbide synthesized in situ by the two to 50% of the final tungsten diboride-silicon carbide composite powder; the carbon source powder A and the carbon source powder B are both carbon black, or both graphite;

[0016] (2) The mixed powder obtained in step (1) is pressed into a green compact by a dry press, placed in a normal pressure and vacuum environment, kept at 1300-1500° C. for 0.5-2 h, then cooled to room temperature, ground into a loose mass and passed through a 200-mesh standard sieve to obtain a tungsten diboride-silicon carbide composite powder of uniform size.

[0017] The purity of the tungsten trioxide powder, boron carbide powder and silicon dioxide powder in step (1) is ≥99%, and the average particle size is 0.1-5 μm; the purity of the carbon source powder A and the carbon source powder B is ≥99%, and the average particle size is 30 nm-1.5 μm.

[0018] The ball milling time in step (1) is 1 to 20 hours, the grinding balls used in the ball milling are made of tungsten carbide, the grinding balls have a diameter of 6.5 to 11 mm, and the ball-to-material mass ratio is (3 to 5):1.

[0019] The volume fraction of silicon carbide in the uniformly sized tungsten diboride-silicon carbide composite powder in step (2) is 5 to 50%; the particle size of the tungsten diboride-silicon carbide composite powder is 0.5 to 2.0 μm.

[0020] A tungsten diboride-silicon carbide composite powder with uniform size prepared by the above preparation method.

[0021] A tungsten diboride-silicon carbide composite ceramic formed by sintering the above-mentioned uniformly sized tungsten diboride-silicon carbide composite powder, wherein the Hv of the composite ceramic is 0.5=24.6±0.7GPa, fracture toughness =5.4±0.7MPa·m 1 / 2 .

[0022] The above-mentioned tungsten diboride-silicon carbide composite ceramic is prepared according to the following method: a tungsten diboride-silicon carbide composite powder is loaded into a graphite mold, and then placed in a spark plasma sintering furnace, and heated to 1500-1700°C at a rate of 50-150°C / min under a vacuum state or with argon as a protective gas, and sintered at a pressure of 10-40MPa for 10-30min, and then cooled to room temperature to obtain a tungsten diboride-silicon carbide composite ceramic.

[0023] The above-mentioned tungsten diboride-silicon carbide composite powder with uniform size is used in the fields of wear-resistant materials, corrosion-resistant materials and cutting tools.

[0024] The above-mentioned tungsten diboride-silicon carbide composite ceramics are used in the fields of wear-resistant materials, corrosion-resistant materials and cutting tools.

[0025] Compared with the prior art, the present invention has the following advantages and effects:

[0026] (1) The raw materials of the present invention, tungsten trioxide, boron carbide, silicon dioxide and carbon source powder, are widely available and inexpensive; the composite powder synthesis process is stable, the yield is high, and it is suitable for large-scale industrial production.

[0027] (2) The present invention uses silicon dioxide as the silicon source. Silicon dioxide, boron carbide and tungsten trioxide react to form tungsten disilicide, such as Figure 6 As shown in XRD, silicon dioxide and boron oxide can effectively avoid the formation of borosilicates that promote the growth of borides and inhibit the formation and growth of silicon carbide. Therefore, the prepared tungsten diboride-silicon carbide composite powder has high purity. Only two phases of tungsten diboride and silicon carbide are detected in XRD and Raman spectra, and no other carbides, graphite or carbon black are detected; the in-situ generated tungsten diboride and silicon carbide powders are small (0.5-2.0μm) and uniform in size, and have good sintering properties.

[0028] WO3+2SiO2+B4C=WSi2+2B2O3+CO(g)#(3)

[0029] 2WSi2+B2O3+7C=2WB+4SiC+3CO(g)#(4)

[0030] 2WB+B2O3+3C=2WB2+3CO(g)#(5)

[0031] (3) The density of the composite ceramic prepared by the present invention is >97%, and the Vickers hardness (Hv 0.5) up to 24.6±0.7GPa, and fracture toughness up to 5.4±0.7MPa·m 1 / 2. Compared with the single-phase tungsten diboride ceramics prepared by the same process (density ≈ 91%, Hv 0.5 =24.4±0.4 GPa), the present invention can realize the low-cost and rapid preparation of dense, high-strength and tough tungsten diboride-silicon carbide composite ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The XRD diagram of the tungsten diboride-silicon carbide composite powder prepared in Examples 1 and 2.

[0033] Figure 2 This is the SEM image of the tungsten diboride-silicon carbide composite powder prepared in Examples 1 and 2.

[0034] Figure 3 This is the XRD diagram of the tungsten diboride-silicon carbide composite ceramics prepared in Examples 3-4.

[0035] Figure 4 This is the Raman graph of the tungsten diboride-silicon carbide composite ceramic prepared in Example 4.

[0036] Figure 5 The SEM images of the tungsten diboride-silicon carbide composite ceramics prepared in Examples 3 to 4 and the EDS results of the corresponding areas.

[0037] Figure 6 : This is the XRD pattern of each raw material powder used in Example 1 after heat treatment at 975°C for 20 minutes. DETAILED DESCRIPTION

[0038] The present invention is further described below with reference to specific embodiments, but they should not be construed as limiting the present invention.

[0039] Example 1

[0040] Tungsten trioxide powder, boron carbide powder and carbon black powder are weighed in a molar ratio of 2:1.05:5; based on the calculation that silicon carbide synthesized in situ from silicon dioxide powder and carbon black powder accounts for 20% of the volume fraction of the final tungsten diboride-silicon carbide composite powder, silicon dioxide powder and carbon black powder are additionally weighed in a molar ratio of 1:3; all the powders weighed above are placed in a ball mill, six carbide grinding balls are added, the ball-to-material ratio is 4:1, and high-energy ball milling is performed for 1 hour under argon protection to obtain a uniform mixed powder.

[0041] The mixed powder is pressed into shape by a dry press and kept at 1400°C for 1 hour under normal pressure and vacuum environment. After cooling to room temperature, the loose block is ground and passed through a 200-mesh standard sieve to obtain tungsten diboride-silicon carbide composite powder.

[0042] Example 2

[0043] The process of preparing the mixed powder is the same as that in Example 1 and will not be described again here.

[0044] The mixed powder is pressed into shape by a dry press, and is vacuum-insulated at 1500° C. for 1 hour under normal pressure and vacuum environment. After cooling to room temperature, the loose block is ground and passed through a 200-mesh standard sieve to obtain tungsten diboride-silicon carbide composite powder.

[0045] Example 3

[0046] The tungsten diboride-silicon carbide composite powder obtained in Example 1 was placed in a graphite mold and sintered in a spark plasma sintering furnace at 1600°C for 10 minutes. The protective atmosphere was argon and the sintering pressure was 30 MPa to obtain a tungsten diboride-silicon carbide composite ceramic. The density of the composite ceramic was measured to be 10.61 g / cm 3 , density is 97.8%, Vickers hardness (Hv 4.9 ) is 24.6±0.7GPa, and the fracture toughness is 5.4±0.7MPa·m 1 / 2.

[0047] Example 4

[0048] The tungsten diboride-silicon carbide composite powder obtained in Example 2 was placed in a graphite mold and sintered in a spark plasma sintering furnace at 1600°C for 10 minutes. The protective atmosphere was argon and the sintering pressure was 30 MPa to obtain a tungsten diboride-silicon carbide composite ceramic. The density of the composite ceramic was measured to be 10.63 g / cm 3 , density is 98.0%, Vickers hardness (Hv 4.9 ) is 22.9±0.5GPa, and the fracture toughness is 4.8±0.5MPa·m 1 / 2.

[0049] Figure 1 The XRD diagram of the tungsten diboride-silicon carbide composite powder synthesized in Examples 1 and 2. It can be seen from the figure that the phase of all samples in XRD is only WB2 type tungsten diboride (P63 / mmc, ICDD PDF#43-1386).

[0050] Figure 2 The SEM images of the tungsten diboride-silicon carbide composite powders synthesized in Examples 1 and 2 and the EDS results of the corresponding regions. Figure 2 It can be seen that the grey phase is tungsten diboride and the black phase is silicon carbide. Figure 2 In (a) and (b), tungsten diboride is mainly in plate form with a particle size of 0.5 to 1.0 μm, and silicon carbide is in irregular granular form with a particle size of 1.0 to 2.0 μm.

[0051] Figure 3 The XRD diagram of the sintered tungsten diboride-silicon carbide composite ceramics of Examples 3 and 4. After the composite powder is sintered, only the diffraction peak of WB2 appears in the XRD.

[0052] Figure 4 is the Raman graph of the tungsten diboride-silicon carbide composite ceramic prepared in Example 4. Figure 4 The Raman results show that the synthesized silicon carbide is 3C-SiC.

[0053] Figure 5 The following are the SEM images of the tungsten diboride-silicon carbide composite ceramics prepared in Examples 3 to 4 and the EDS results of the corresponding areas. As can be seen from the figure, the gray phase is tungsten diboride and the black phase is silicon carbide. There are no obvious pores in the tungsten diboride-silicon carbide composite ceramics, and the interface between the two phases is well bonded. Tungsten diboride and silicon carbide are evenly distributed, and the grain size is small (≤1.5μm).

[0054] Figure 6 This is the XRD result of the raw material powders used in Example 1 after heat treatment at 975°C for 20 minutes. It can be seen from the figure that the main phases of the powders are W, WC, W2C and WSi2, indicating that the intermediate product WSi2 will be produced during the synthesis of WB2 from WO3, SiO2, B4C and carbon black in the raw materials, which can effectively avoid the formation of borosilicate.

[0055] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing tungsten diboride-silicon carbide composite ceramics, characterized in that The steps include: (1) Weigh tungsten trioxide powder, boron carbide powder and carbon source powder A in a molar ratio of 2: (1 ~ 1.2): (4.7 ~ 5); then weigh silicon dioxide powder and carbon source powder B in a molar ratio of 1:3; fully mix all the above-mentioned powders by ball milling at room temperature using a high-energy ball mill to obtain a mixed powder; the weighed amounts of the silicon dioxide powder and the carbon source powder B are calculated based on the volume fraction of the silicon carbide synthesized in situ by the two to 50% of the final tungsten diboride-silicon carbide composite powder; the carbon source powder A and the carbon source powder B are both carbon black, or both graphite; (2) using a dry press to press the mixed powder obtained in step (1) into a green compact, placing it in a normal pressure and vacuum environment, keeping it at 1300-1500°C for 0.5-2 h, then cooling it to room temperature, grinding the loose block and passing it through a 200-mesh standard sieve to obtain a tungsten diboride-silicon carbide composite powder of uniform size; (3) The tungsten diboride-silicon carbide composite powder is loaded into a graphite mold, and then placed in a spark plasma sintering furnace. Under vacuum or with argon as a protective gas, the temperature is raised to 1500-1700°C at a rate of 50-150°C / min, and the temperature is kept at 10-40 MPa for 10-30 min for sintering, and then cooled to room temperature to obtain tungsten diboride-silicon carbide composite ceramics; The tungsten diboride-silicon carbide composite ceramic has a density of > 97%, a Vickers hardness of up to 24.6 ± 0.7 GPa, and a fracture toughness of up to 5.4 ± 0.7 MPa·m 1 / 2 .

2. The preparation method according to claim 1, characterized in that: The purity of the tungsten trioxide powder, boron carbide powder and silicon dioxide powder in step (1) is ≥99%, and the average particle size is 0.1 ~ 5 μm; the purity of the carbon source powder A and the carbon source powder B is ≥99%, and the average particle size is 30 nm ~1.5 μm.

3. The preparation method according to claim 1, characterized in that: The ball milling time in step (1) is 1 to 20 hours, the grinding balls used in the ball milling are made of tungsten carbide, the grinding balls have a diameter of 6.5 to 11 mm, and the ball-to-material mass ratio is (3 to 5):

1.

4. The preparation method according to claim 1, characterized in that: The volume fraction of silicon carbide in the uniformly sized tungsten diboride-silicon carbide composite powder in step (2) is 5 to 50%; and the particle size of the tungsten diboride-silicon carbide composite powder is 0.5-2.0 μm.

5. A tungsten diboride-silicon carbide composite ceramic prepared by the preparation method according to any one of claims 1 to 4.

6. Application of the tungsten diboride-silicon carbide composite ceramic according to claim 5 in the fields of wear-resistant materials, corrosion-resistant materials and cutting tools.

Citation Information

Patent Citations

  • Preparation method of zirconium boride-silicon carbide complex phase high temperature resistance powder material

    CN102826851A

  • An ultrafine zirconium diboride-silicon carbide composite powder and its preparation method

    CN108622911B

  • Flaky tungsten diboride powder containing defects as well as preparation method and application of flaky tungsten diboride powder

    CN115385695A

  • Manufacturing method of zirconium diboride-silicon carbide composite

    KR1020110077154A